TINJAUAN YURIDIS TERHADAP KEDUDUKAN ANAK DARI PERKAWINAN SIRI MENURUT KOMPILASI HUKUM ISLAM - Dearma sinaga (Universitas Harapan Medan, 2020)
The nature of marriage is a legal relationship between subjects who are bound in marriage (in this case what is meant is between a man and a woman). Marriage under Marriage Law No. 1 of 1974 is considered as an agreement (agreement) provided that the word agreement is taken in a broad sense. Because to get married requires a corresponding will between a man and a woman as well as information about the existence of the will. The term siri or secret marriage is already known among the ulemas. It's just that siri marriage which was known in the past is different in understanding from siri marriage at the present time. Previously what was meant by siri marriage is marriage in accordance with the pillars of marriage and the conditions according to the Shari'ah, it's just that witnesses were asked not to notify the occurrence of the marriage to the public, to the public, and naturally there was no walimatul-ursy. The siri marriage known by the people of Indonesia today is a marriage carried out by a guardian or deputy guardian and witnessed by witnesses, but not performed before the Marriage Registrar as an official government official or not registered at the Office of Religious Affairs for those who are Muslim or in Civil Registry Office for non-Muslims.The research method used in the preparation of this study is a qualitative method. A good study always pays attention to the suitability of the techniques used with general thought flow and theoretical ideas. The word 'qualitative method' can be interpreted as a technique or procedure and a theoretical idea. In the context of qualitative research, they presuppose each other. For example, in the foregoing descriptions it will be explained that the purpose of using qualitative methods is to seek a deep understanding of a phenomenon, fact or reality. Facts, reality, problems, symptoms and events can only be understood if the researchers trace them internally and are not limited to surface views.Legislation in force in Indonesia does not recognize the term children born as a result of a marital siri, besides that there is also no mention of the meaning of the term out of wedlock, in the legislation only mentions the notion of a legitimate child, which is contained in article 42 The Marriage Law states that the definition of a legitimate child is a child born as a result of a legal marriage, and article 99 KHI states the understanding of a legitimate child that is a child born as a result of a legal marriage or the result of fertilization between a legitimate husband and wife outside the wife's womb and born by the wife, so to find out the meaning of children outside of marriage must be forced to understand with the opposite meaning to these articles, namely that the child outside of marriage is a child who was not born in or as a result of a legal marriage or child which is not produced from fertilization legal husband and wife outside the womb and born by the wife.